Bronchodilating effects of bambuterol on bronchoconstriction in guinea pigs - Xie Qiang-min; Zeng Ling-hui; Zheng Yi-xiong; Lu Yun-bi; Yang Qiu-huo (Acta Pharmacologica Sinica; Vol 20, No 7 (July 1999): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of bambuterol (Bam) on bronchoconstriction in guinea pigs. METHODS: Bronchospasm induced by histamine aerosol, lung resistance (RL) and dynamic lung compliance (Cdyn) changes induced by ovalbumin aerosol in vivo, isolated resting lung parenchyma strips, and carbamylcholine-induced tracheal constriction in vitro in guinea pig were investigated. RESULTS: Bam dose-dependently prolonged the time to histamine-induced collapse, ED50 values (95% confidence limits) of Bam intragastric gavage (i.g.) after 1 h, 4 h, and 24 h were 0.74 (0.60-0.91), 0.75 (0.61-0.91) and 1.00 (0.77-1.30) mg.kg-1, respectively. Bam 2 or 10 mg.kg-1 i.g. 2 h before ovalbumin aerosol partly or almost completely inhibited bronchial challenge of ovalbumin-induced change of RL and Cdyn. Bam 0.1-1.0 mumol.L-1 gave a weak relaxation on isolated tracheal strips induced by carbamylcholine and failed to relax the isolated resting lung parenchyma strips in guinea pig. CONCLUSION: Bam showed a long-acting bronchodilation by its slow metabolism in vivo.